Penerapan Metode Pembelajaran Sugestopedia dalam Meningkatkan Kemampuan Menghafal Mufradat Peserta Didik Kelas VIII MTs DDI Kanang - Amir, Muhammad Aswar; Herdah,; Musyarif,; Darmawati,; Kaharuddin, (Shaut al Arabiyyah, 2025)
The suggestopedia method is applied to transform and create a relaxed learning environment for students, eliminating any tension during the learning process. The implementation of the suggestopedia method aimed to enhance the memorization skills of mufradat for Grade VIII students at MTs DDI Kanang. This was prompted by the observation that many students struggled with mastering mufradat. The main issue addressed in this research was how to implement the suggestopedia learning method to improve students' memorization skills of mufradat. This research adopted a quantitative approach with a quasi-experimental design called the Non-Equivalent Control Group Design. Data collection involved administering multiple-choice tests (pre-test and post-test), treatments, observations, and documentation. The data analysis techniques employed were descriptive analysis and inferential analysis (analysis requirements test and hypothesis testing). The research findings revealed the following: 1) There was an influence of the suggestopedia learning method on the improvement of students' memorization skills of mufradat for Grade VIII at MTs DDI Kanang, as evidenced by the pre-test score of 58.12 and the post-test score of 85.49 with a paired samples test resulting in a Sig. value of 0.000. 2) There was an influence of the drill method on the improvement of students' memorization skills of mufradat for Grade VIII at MTs DDI Kanang, as indicated by the pre-test score of 51.84 and the post-test score of 78.55 with a paired samples test resulting in a Sig. value of 0.000. 3) There was a difference in the improvement of memorization skills of mufradat between the suggestopedia learning method and the drill learning method for Grade VIII students at MTs DDI Kanang, supported by the independent samples test with a Sig. value of 0.000.